2020 IEEE 17th International Symposium on Biomedical Imaging (ISBI) 2020
DOI: 10.1109/isbi45749.2020.9098327
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Networks for Compressive Video Reconstruction

Abstract: Single-pixel imaging allows low cost cameras to be built for imaging modalities where a conventional camera would either be too expensive or too cumbersome. This is very attractive for biomedical imaging applications based on hyperspectral measurements, such as image-guided surgery, which requires the full spectrum of fluorescence. A single-pixel camera essentially measures the inner product of the scene and a set of patterns. An inverse problem has to be solved to recover the original image from the raw measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Figure 2b shows a 101 × 101 pixels measurement obtained over 4 h. The acquisition time can be reduced by three complementary optimizations, namely algorithmic, electronical, and optical optimizations. The algorithmic improvement of compressive sensing acquisitions is an active field of studies [15,23,24]. Fourier patterns are used in the study for the sake of simplicity but could be benchmarked against the basis of other patterns and reconstruction strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2b shows a 101 × 101 pixels measurement obtained over 4 h. The acquisition time can be reduced by three complementary optimizations, namely algorithmic, electronical, and optical optimizations. The algorithmic improvement of compressive sensing acquisitions is an active field of studies [15,23,24]. Fourier patterns are used in the study for the sake of simplicity but could be benchmarked against the basis of other patterns and reconstruction strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that feedback mechanisms have been applied to a variety of computer vision tasks [37][38][39][40]. For the SPI task, Antonio et al used an RNN network with temporal memory to control the delivery and loss of features [41]. Ikuo et al improved the quality of the reconstructed images by chunking the measurement data input and accumulating and updating them in an RNN [42].…”
Section: Feedback Mechanismmentioning
confidence: 99%
“…Recently, deep neural networks have been used successfully in signal pixel imaging reconstruction problems. In [66], A. l. Mur et al have exploited the spatio-temporal features of video and proposed a Convolutional Gated Recurrent Units (ConvGRU) based algorithm to reconstruct video frames already captured by a single pixel camera. N. Ducros et al [67] defined a generic convolutional network to recover the original video.…”
Section: Single Pixel Imagingmentioning
confidence: 99%